Evaluasi efektivitas padat tebar yang berbeda pada sistem ekstensif polikultur terhadap pertumbuhan dan kualitas agar rendemen rumput laut (Gracilaria verrucosa): Assessment of varying stocking densities in extended polyculture systems on the development and yield quality of seaweed (Gracilaria verrucosa) - Fitriyanti Putri Permata Sari; Andi Rahmad Rahim (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2025)
Gracilaria verrucosa is a kind of seaweed with significant potential for pond culture, particularly among farmers, since it serves as the primary source of agar production, which is experiencing rising demand. Nonetheless, pond output remains insufficient to satisfy market demands, necessitating innovation in cultivation methods and enhanced production efficiency. The researcher intends to assess the efficacy of various stocking densities in an extended polyculture system on the growth and quality of agar production from Gracilaria verrucosa seaweed. This research employs a quantitative approach utilizing an experimental methodology. This study had a fully randomized design (CRD) with three treatments, each replicated three times. Treatment A (Density 150 g/cm³), Treatment B (Density 200 g/cm³), Treatment C (Density 250 g/cm³). This study method employs a test medium container designed as a net, into which seaweed lips are placed, followed by a 35-day observation of growth. Data analysis was conducted utilizing analysis of variance, succeeded by the Tukey test, with a confidence level of 95% (p<0.05). Varied stocking densities influenced the development of Gracilaria verrucosa, the effectiveness of good stocking density in treatment A (150g) obtained the highest absolute length of 8g for 35 days.